Предмет: Алгебра,
автор: alexander49
Пожалуйста 2 задание
Приложения:
Ответы
Автор ответа:
0
(g(x)*f(x))' - g(x) * f'(x) = g'(x) * f(x) + g(x) * f'(x) - g(x) * f'(x) = g'(x) * f(x)
g(x) = x^2 - 8
f(x) = 2x+4
g'(x) = 2x
Тогда g'(x) * f(x) = 2x*(2x+4),
g'(2.5) * f(2.5) = 2 * 2.5 * (2 * 2.5 + 4) = 45
g(x) = x^2 - 8
f(x) = 2x+4
g'(x) = 2x
Тогда g'(x) * f(x) = 2x*(2x+4),
g'(2.5) * f(2.5) = 2 * 2.5 * (2 * 2.5 + 4) = 45
Автор ответа:
0
f(x)=2x+4
g(x)=x^2-8
1)(g(x)*f(x))'=((2x+4)(x^2-8))'=(2x^3-16x+4x^2-32)'=6x^2+8x-16
2)f'(x)=(2x+4)'=2
(g(x)*f(x))'-g(x)*f'(x)= 6x^2+8x-16-2(x^2-8)=6x^2+8x-16-4x^2+16=
=4x^2+8x=4x(x+2)=4*2,5(2,5+2)=45
g(x)=x^2-8
1)(g(x)*f(x))'=((2x+4)(x^2-8))'=(2x^3-16x+4x^2-32)'=6x^2+8x-16
2)f'(x)=(2x+4)'=2
(g(x)*f(x))'-g(x)*f'(x)= 6x^2+8x-16-2(x^2-8)=6x^2+8x-16-4x^2+16=
=4x^2+8x=4x(x+2)=4*2,5(2,5+2)=45
Похожие вопросы
Предмет: Алгебра,
автор: Аноним
Предмет: Английский язык,
автор: marinabaroeva8
Предмет: Русский язык,
автор: sport549
Предмет: Математика,
автор: kotrin
Предмет: Математика,
автор: khghxdjhxv